Proposed mechanisms for oligonucleotide IMT504 induced diabetes reversion in a mouse model of immunodependent diabetes - Bianchi, Maria Silvia (2016)
Type 1 diabetes (T1D) originates from autoimmune β-cell destruction. IMT504 is an immunomodulatory oligonucleotide that increases mesenchymal stem cells cloning capacity and reverts toxic diabetes in rats. Here we evaluated long-term (20 doses) and short-term (2-6 doses) effects of IMT504 (20 mg/kg/day, sc) in an immunodependent diabetes model: multiple low dose streptozotocin-injected BALB/c mice (40 mg/kg/day, i.p. for 5 consecutive days). We determined blood glucose, glucose tolerance, serum insulin, islet morphology, islet infiltration, serum cytokines, progenitor cell markers, immunomodulatory proteins, proliferation, apoptosis, and islet gene expression. Long-term results: IMT504 reduced glycemia, induced β-cell recovery and impaired islet infiltration. Short-term analysis: IMT504 induced early blood glucose decrease, infiltration inhibition, increased β-cell proliferation and decreased apoptosis, increased islet indoleamine 2,3-dioxygenase (IDO) expression, increased serum tumor necrosis factor and interleukin-6 (IL-6). IMT504 affected islet gene expression: Preproinsulin-2, Proglucagon, Somatostatin, Nestin, Regenerating gene-1 and C-X-C motif ligand-1 cytokine (Cxcl1) increased in islets from diabetic mice and were decreased by IMT504. IMT504 downregulated Platelet endothelial cell adhesion molecule-1 (Pecam1) in islets from control and diabetic mice, whereas it increased Regenerating gene-2 (Reg2) in islets of diabetic mice. The IMT504-induced increase in IL-6 and islet IDO expression, and decreased islet Pecam1 and Cxcl1 mRNA expression could participate in keeping leukocyte infiltration at bay, whereas upregulation of Reg2 may mediate β-cell regeneration. We conclude that IMT504 effectively reversed immunodependent diabetes in mice. Corroboration of these effects in a model of autoimmune diabetes more similar to human T1D could provide promising results for the treatment of this disease.